Avaliação da capacidade antioxidante do colostro de puérperas internadas em uma maternidade de alto risco - Vieira, Ana Paula de Bulhões (2018)
Breast milk-character, of many advantages, its antioxidant properties. Studies indicate that all factors, conditions and problems that affect health are the results of free radical imbalance. When the increased production of free radicals and decreased antioxidants has developed, a condition of oxidative stress develops, can generate serious seriousness in childhood. Antioxidant drinks increase the pressure and increase as antioxidants in babies, especially premature babies. The antioxidant mining of breast milk will allow an overall characterization of its value, allowing a minimization of the oxidative stress of newborns. In this way, the interest arises in determining a total antioxidant capacity of breast milk. The present study aims to define the antioxidant capacity of breast milk and to relate to maternal and newborn variables. The measurement was initiated and collected with the volume and volume of 1ml of colostrum of each participant. The analyzes were performed using the DPPH method and the results were reported on maternal variables (weight and length at birth). In a between maternal milk antioxidant ability and BMI categories, it was found that the differences were significant when it came to prepregnancy BMI, where a median of AC in overweight women differed from obese women, categorized as eutrophic have an intermediate behavior between being overweight and obese. In the evaluations between AC and maternal-infant variables it was verified that there was no significant significance. An analysis of antioxidant capacity and control over the variables of food consumption, fast, efficient and effective in relation to society. Colostrum from the women evaluated the potential antioxidant, non-existent difference between maternal variables and the newborn.